Education on Sports Injury Prevention and Management for Physical Education Teachers and School Health Unit (UKS) Members in Jeumpa District, Bireuen Regency - Muhamad Reza; Dedi Saputra; Novida Humaira (Jurnal Pengabdian Pemersatu Bangsa, 2026)
Sports injuries are among the most common risks encountered during Physical Education, Sports, and Health (PESH) classes and extracurricular sports activities in schools. Limited knowledge of physical education teachers and School Health Unit (UKS) members regarding injury prevention and initial management may increase the likelihood of inappropriate first-aid practices. This community service program aimed to improve the knowledge and practical skills of physical education teachers and UKS members in preventing and managing sports injuries in the school environment. The program was conducted in Jeumpa District, Bireuen Regency, using a participatory educational approach consisting of lectures, interactive discussions, demonstrations, hands-on practice, and evaluation through pre-tests and post-tests. The educational materials included sports injury risk factors, prevention strategies, first-aid procedures based on the Protection, Rest, Ice, Compression, and Elevation (PRICE) principle, and basic splinting techniques. The evaluation results indicated a significant improvement in participants' knowledge, with the average score increasing from 61.2% in the pre-test to 91.6% in the post-test, representing an improvement of 30.4%. Participants also demonstrated better practical skills in performing appropriate first-aid procedures for sports injuries. Overall, the program successfully enhanced the competence of physical education teachers and UKS members in promoting a safer and healthier school environment with improved preparedness for sports injury management.